2010
DOI: 10.1007/s00441-010-0943-2
|View full text |Cite
|
Sign up to set email alerts
|

Temporal alterations in cardiac fibroblast function following induction of pressure overload

Abstract: Increases in cardiovascular load (pressure overload) are known to elicit ventricular remodeling including cardiomyocyte hypertrophy and interstitial fibrosis. While numerous studies have focused on the mechanisms of myocyte hypertrophy, comparatively little is known regarding the response of the interstitial fibroblasts to increased cardiovascular load. Fibroblasts are the most numerous cell type in the mammalian myocardium and have long been recognized as producing the majority of the myocardial extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…Here, we demonstrated that leptin promotes cardiac fibroblast migration, an observation consistent with results in other cell types, including endothelial cells (31) and tumor cells of various origins (32,33). This altered rate of migration via leptin may have many implications in vivo, namely enhanced collagen deposition in the injury zone in various cardiac pathologies, which may accelerate the transition to HF (5,7,8). Inhibition of Rho activation prevented leptin-stimulated fibroblast migration, and a schematic diagram summarizing the various effects of leptin and how they may be connected is shown as Fig.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Here, we demonstrated that leptin promotes cardiac fibroblast migration, an observation consistent with results in other cell types, including endothelial cells (31) and tumor cells of various origins (32,33). This altered rate of migration via leptin may have many implications in vivo, namely enhanced collagen deposition in the injury zone in various cardiac pathologies, which may accelerate the transition to HF (5,7,8). Inhibition of Rho activation prevented leptin-stimulated fibroblast migration, and a schematic diagram summarizing the various effects of leptin and how they may be connected is shown as Fig.…”
Section: Discussionsupporting
confidence: 78%
“…However, alternate cardiac cell types, including cardiomyocytes and endothelial cells, also represent a source of these structural proteins and therefore contribute to maintenance of the ECM (4). Subsequent to cardiac injury, the proliferative and migratory responses of cardiac fibroblasts are activated and can result in fibrosis (5), which is characterized as either reparative or reactive. Reactive fibrosis involves enhanced collagen accumulation in the interstial or perivascular space, whereas reparative fibrosis replaces apoptotic/necrotic cardiomyocytes (6).…”
mentioning
confidence: 99%
“…A scratch assay was used to evaluate the potential modulation of the migratory ability of cardiac fibroblasts by IL-33 [47, 59]. A denuded area was introduced in the center of confluent cultured fibroblasts and the ability of fibroblasts to migrate into the denuded area measured following treatment of the cells with different doses of IL-33 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cardiac fibroblasts interact with the surrounding ECM and are integral to the organization of tissue architecture and support of basic cellular functions, including survival, proliferation and migration [39]. Accordingly, increased collagen production would not only be expected to cause structural rearrangements in the myocardium, but also modifications in fibroblast-ECM interactions.…”
Section: Discussionmentioning
confidence: 99%